1998
DOI: 10.1523/jneurosci.18-01-00294.1998
|View full text |Cite
|
Sign up to set email alerts
|

Blockade and Recovery of Spontaneous Rhythmic Activity after Application of Neurotransmitter Antagonists to Spinal Networks of the Chick Embryo

Abstract: We studied the regulation of spontaneous activity in the embryonic (day 10-11) chick spinal cord. After bath application of either an excitatory amino acid (AP-5 or CNQX) and a nicotinic cholinergic (DHbetaE or mecamylamine) antagonist, or glycine and GABA receptor (bicuculline, 2-hydroxysaclofen, and strychnine) antagonists, spontaneous activity was blocked for a period (30-90 min) but then reappeared in the presence of the drugs. The efficacy of the antagonists was assessed by their continued ability to bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
171
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 45 publications
15
171
2
Order By: Relevance
“…Generation of this LF activity in the embryonic mouse brainstem does not seem to rely on single anatomical structures or specific circuits, because it was observed in both facial and medullary slices. Spontaneous activity occurring at low rate and invading large territories has been described in various species and a wide variety of developing structures in the CNS such as the spinal cord (O'Donovan and Landmesser, 1987;Chub and O'Donovan, 1998;O'Donovan, 1999;Branchereau et al, 2000;Hanson and Landmesser, 2003;Ren and Greer, 2003;Yvert et al, 2004), the cortex (Garaschuk et al, 2000;Peinado, 2000), the hippocampus (Ben-Ari, 2001), the retina (Galli and Maffei, 1988;Katz and Shatz, 1996), and the brainstem (Fortin et al, 1994;Abadie et al, 2000;Gust et al, 2003). The LF activity observed in the present study probably corresponds to an immature activity.…”
Section: Lf Activity Is a Primordial Activitysupporting
confidence: 59%
“…Generation of this LF activity in the embryonic mouse brainstem does not seem to rely on single anatomical structures or specific circuits, because it was observed in both facial and medullary slices. Spontaneous activity occurring at low rate and invading large territories has been described in various species and a wide variety of developing structures in the CNS such as the spinal cord (O'Donovan and Landmesser, 1987;Chub and O'Donovan, 1998;O'Donovan, 1999;Branchereau et al, 2000;Hanson and Landmesser, 2003;Ren and Greer, 2003;Yvert et al, 2004), the cortex (Garaschuk et al, 2000;Peinado, 2000), the hippocampus (Ben-Ari, 2001), the retina (Galli and Maffei, 1988;Katz and Shatz, 1996), and the brainstem (Fortin et al, 1994;Abadie et al, 2000;Gust et al, 2003). The LF activity observed in the present study probably corresponds to an immature activity.…”
Section: Lf Activity Is a Primordial Activitysupporting
confidence: 59%
“…Embryonic movements are likely to be a reliable indicator of spinal SNA because electromyographic recordings in ovo during embryonic movements are remarkably similar to motoneuron recordings during in vitro SNA (30)(31)(32)(33). It is also likely that SNA that recovers after antagonist injections in the egg is similar to SNA before the antagonists were added because similar findings have been observed in the in vitro spinal cord preparation (22). Further, we did not observe differences in several features of the in ovo embryonic movements in treated and control embryos, including total movement duration, bout duration, bout frequency, or recovery of the movements.…”
Section: Discussionmentioning
confidence: 59%
“…Doubling the concentration of any drug or the addition of a second bolus at E9 produced no additional effect on limb movements (data not shown). This finding suggested that the drugs were still effective but that the spinal networks controlling limb movements had compensated for the loss of transmission (22). These experiments demonstrate that GABA A or AMPA/NMDA receptor activation can be significantly reduced in ovo from E8 to E10, whereas levels of SNA remained largely intact, apart from a transient reduction after drug administration.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations